Factors that Influence the Quality of Audit with Professional Ethics as a Moderating Variable (Study at Public Accounting Firms in Bekasi) - Ria Ria; Bambang Subiyanto; Arni Karina; Nabila Prillia Tasya (Budapest International Research and Critics University, 2022)
This study aims to analyze and obtain empirical evidence regarding the factors influencing audit quality with professional ethics as a moderating variable. The variables used are auditor experience, independence, and objectivity as independent variables, while the dependent variable is audit quality and professional ethics as moderating variables—analyzed using WarpPLS 7.0 program. Sources of data in this study used primary data in the form of a questionnaire in data collection of as many as 12 Public Accounting Firms in Bekasi Regency and City. Then, this research data was given to 100 respondents. In taking the sample of this study using purposive sampling. The analytical technique used in this research is regression analysis using the WarpPLS 7.0 program. Based on the results of this study, it can be shown that the auditor's experience, independence, and objectivity have a positive effect. Then auditor ethics can strengthen the effect of auditor experience on audit quality. Meanwhile, professional ethics can weaken the influence of independence and objectivity on audit quality.